2018
DOI: 10.1152/ajpcell.00153.2017
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine acts via MrgD to induce AMPK/NO activation against ANG II hypertrophy in cardiomyocytes

Abstract: The renin-angiotensin system (RAS) plays a pivotal role in the pathogenesis of cardiovascular diseases. New members of this system have been characterized and shown to have biologically relevant actions. Alamandine and its receptor MrgD are recently identified components of RAS. In the cardiovascular system, alamandine actions included vasodilation, antihypertensive, and antifibrosis effects. Currently, the actions of alamandine on cardiomyocytes are unknown. Here our goal was twofold: 1) to unravel the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
0
47
0
3
Order By: Relevance
“…Alternatively , angiotensin II can be processed by aspartate decarboxylase (AD) to produce angiotensin A , which can be converted to alamandine by ACE2. Upon binding to the Mas-related G protein-coupled receptor member D (MRGD), alamandine can promote the same effects reported for angiotensin 1-7 5,67,190 , with the exception of natriuresis. RAS, renin-angiotensin system.…”
Section: Key Pointsmentioning
confidence: 72%
See 2 more Smart Citations
“…Alternatively , angiotensin II can be processed by aspartate decarboxylase (AD) to produce angiotensin A , which can be converted to alamandine by ACE2. Upon binding to the Mas-related G protein-coupled receptor member D (MRGD), alamandine can promote the same effects reported for angiotensin 1-7 5,67,190 , with the exception of natriuresis. RAS, renin-angiotensin system.…”
Section: Key Pointsmentioning
confidence: 72%
“…This mechanism might contribute to the anti hypertrophic properties of angiotensin 1-7, given that neither activation of the AT 1 R nor the proto oncogene Mas receptor antagonists prevented the bene ficial effects of this peptide 4 . Alamandine activates the AMPactivated protein kinase (AMPK)-nitric oxide (NO) pathway via the Mas related G protein coupled recep tor member D (MRGD), which prevents angiotensin II induced hypertrophy 5 . By contrast, angiotensin 1-9 stimulates the AT 2 R-AKT signalling pathway to pro tect the myocardium against reperfusion induced cell death 6 .…”
Section: Components Of the Counter-regulatory Ras Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alamandine acts on the MrgD and expresses similar effects to Ang (1-7) [128,136]. Recent research claimed that alamandine could activate AMPK in ventricular cardiomyocytes via MrgD [89]. Alamandine also induced a significant increase in LKB1 phosphorylation.…”
Section: Mas or Mrgd Receptor And Ampkmentioning
confidence: 97%
“…Chen et al [88] reported that when H9C2 cells were co-cultured with 5 μM of AngII for 12, 24, or 48 h, autophagy was enhanced, while AMPKα/mTOR signaling or cellular ADP/ATP ratio was not impacted. In another study, neonatal rat cardiomyocytes (NRCMs) were treated with AngII (100 nmol/l) for 36 h. The results showed that AngII did not affect the phosphorylation of AMPK [89]. Kim et al [90] claimed that by activating the AT1R-calcium-AMPK-JNK axis pathway, AngII induces inflammation in atrial cells.…”
Section: Angii and Ampk In Heartmentioning
confidence: 99%